José Bonifácio, humanista - Pereira, Nilo (Ciência & Trópico, 2011)
RESUMOConsiderações sobre a figura de José Bonifácio de Andrada e Silva, Patriarca da Independência do Brasil, seu interesse pelos aspectos múltiplos do conhecimento científico e das artes, e sua capacidade prospectiva em relação ao desenvolvimento do Brasil.ABSTRACTJosé Bonifácio, humanist. v. 1, n. 2, p. 261-269, jul./dez. 1973.Considerations about the personality of José Bonifácio de Andrada e Silva, the Father leader man in the Independence of Brazil, his interest by several aspects of the scientific knowledge and the arts, and his prospective capacity in relation to the development of Brazil.RESUMÉJosé Bonifácio, humaniste. v. 1, n. 2, p. 261-269, jul./dez. 1973.Considérations sur la figure de José Bonifácio de Andrade e Silva, Patriarche de l’Indépendance du Brésil, son intéret par les aspects multiples de la connaissance scientifique et par les arts, et sa capacité prospective par rapport au développement du Brésil.